2004
DOI: 10.4040/jkan.2004.34.7.1184
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Uncertainty, Hope and Quality of Life in Patients with Breast Cancer

Abstract: Based on the study results, breast cancer patients experienced living with uncertainty and maintaining hope. Thus the study's findings can be useful in directing a comprehensive nursing care plan to improve QOL of breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 1 publication
0
14
0
2
Order By: Relevance
“…[27] Jo and Son's study (2004) of cancer patients' QOL, hope, and uncertainty found a similar result. [28] Arslantaş et al (2010) also found moderate levels of hope in a study conducted with in-patients. [24] The results of the present study and other research are similar.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…[27] Jo and Son's study (2004) of cancer patients' QOL, hope, and uncertainty found a similar result. [28] Arslantaş et al (2010) also found moderate levels of hope in a study conducted with in-patients. [24] The results of the present study and other research are similar.…”
Section: Resultsmentioning
confidence: 97%
“…[24] The results of the present study and other research are similar. [24,27,28] Hope levels of patients are higher than moderate level when they were expected to be low. Hope scores may have been higher than moderate level because hope is a factor that improves motivation for treatment.…”
Section: Resultsmentioning
confidence: 98%
“…The majority of the studies (N=31) were conducted in East Asia, with 3 from mainland China, 46 53 54 2 from Hong Kong, 35 39 11 from Taiwan, 15 41 51 52 55–61 8 from Korea 42–44 48 49 62–64 and 7 from Japan. 36–38 40 45 50 65 Only one study was conducted in Southeast Asia (Malaysia).…”
Section: Resultsmentioning
confidence: 99%
“…Education, employment and economic status were more consistently associated with hope and hopelessness. Twelve studies examined education, with significant associations reported in 10 studies; education was positively correlated with hope 41 42 52 58 60 62 and negatively associated with hopelessness. 37 38 47 53 Six of 10 studies reported significant associations between employment status and hope; patients who were employed had higher hope 42 52 58 60 and lower hopelessness.…”
Section: Resultsmentioning
confidence: 99%
“…그 동안 암 환자를 비롯한 신체질환자들의 가족들을 대상으로 불확실성 에 영향을 주는 요인을 확인하는 연구들이 대부분이었다 (Jo & Son, 2004;Kang, 2011;Ko & Hsu, 2005;Mishel et al, 2009 (Bai, 2001;Ha, 2001;Lee & Park, 2003;Szmukler et al, 1996) (Table 2). (Mishel, 1988;Mishel, 1997;Mishel et al, 2005;Mishel et al, 2009) (Ham, Kim, & Park, 2000;Mishel, 1997;Yoo, 1996).…”
unclassified